ANALISIS KONDISI KESEHATAN DALAM KONTEN BERITA BINTANG BORNEO TAHUN 1928 - Aulia Rahuma; Rahmayanti, Sri; Moh Bahzar (History Education Department, Universitas Mulawarman, 2023)
Health conditions in the content analysis of Bintang Borneo in 1928 is a topic that reflects an important aspect in the history of public health in the Borneo region in that period. This analysis reveals information about health problems, disease prevention efforts, and community responses to health issues in 1928. The historical data shows that during that time, communities in Borneo faced serious challenges related to infectious diseases, limited access to medical care, and social and economic changes that affected health well-being. Further research in this context can provide valuable insights into how health conditions have evolved and inspire a deeper understanding of social change and healthcare in the region.